Self-assembled monolayers of shape-persistent macrocycles on graphite: interior design and conformational polymorphism - Vollmeyer, Joscha; Eberhagen, Friederike; Höger, Sigurd; Jester, Stefan-S. (Beilstein Journal of Organic Chemistry, 2014)
Three shape-persistent naphthylene–phenylene–acetylene macrocycles of identical backbone structures and extraannular substitution patterns but different (empty, apolar, polar) nanopore fillings are self-assembled at the solid/liquid interface of highly oriented pyrolytic graphite and 1,2,4-trichlorobenzene. Submolecularly resolved images of the resulting two-dimensional (2D) crystalline monolayer patterns are obtained by in situ scanning tunneling microscopy. A concentration-dependent conformational polymorphism is found, and open and more dense packing motifs are observed. For all three compounds alike lattice parameters are found, therefore the intermolecular macrocycle distances are mainly determined by their size and symmetry. This is an excellent example that the graphite acts as a template for the macrocycle organization independent from their specific interior.
Keywords: conformational polymorphism; self-assembled monolayers; shape-persistent macrocycles; solid/liquid interface; supramolecular surface patterning; template